Privatization and economic efficiency : a comparative analysis of developed and developing countries - Ott, Attiat F.; Hartley, Keith (E. Elgar Pub., 1991)
A series of case studies examines the theory, evidence and policy experience of privatization in developed and developing nations. These studies focus on the UK, US, Egypt and Jamaica. The book concludes that privatization is an appealingly simple phrase concealing many difficulties and problems for analysts, researchers and policymakers.